A entrada de franquias americanas no Brasil: uma estratégia diferente - Gurtner, Werner Frank (1997)
Written for an American audience, highlights administrative and cultural peculiarities of the Brazilian fast food marketplace. Uses examples of American franchise entrance procedures and resulting successes and failures. Particular focus is placed on their administrative performance while in Brazil. Discusses alternative strategies for future international expansion by American franchises